Bilateral ramus mandibulectomy with plate reconstruction in ameloblastic carcinoma patient - Eunike Lay; Widodo Ario Kentjono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Ameloblastic carcinoma is a rare and malignant odontogenic tumour possibly arising de-novo from pre-existing ameloblastoma. It is aggressive and locally destructive. Ameloblastoma is the most common benign odontogenic tumour of the mandible. It originates from the tooth-forming epithelium, where its aetiology remains unknown. Ameloblastoma usually grows slowly, is asymptomatic, and destroys the surrounding bone tissue. Malignant transformation of ameloblastomas may occur spontaneously. Resection is the primary therapy for ameloblastic carcinoma with extensive bone destruction. Mandibular resection causes instability due to the missing parts of bone, so reconstruction is needed. Purpose: This study will report on an individual case of ameloblastic carcinoma that underwent a bilateral ramus mandibulectomy with reconstruction using the plate technique. Case: Bilateral ramus mandibulectomy with plate and reconstruction in an ameloblastic carcinoma patient. Case Management: Two months after surgery, the patient could open her mouth functionally and aesthetically. Conclusion: Plate reconstruction is an option for reconstructing bilateral ramus mandibulectomy of a large ameloblastic carcinoma of the mandible.